2019
DOI: 10.1039/c8ra09884k
|View full text |Cite
|
Sign up to set email alerts
|

Highly diastereoselective construction of novel dispiropyrrolo[2,1-a]isoquinoline derivativesviamulticomponent 1,3-dipolar cycloaddition of cyclic diketones-based tetrahydroisoquinoliniumN-ylides

Abstract: A new series of dispiropyrrolo[2,1-a]isoquinoline derivatives was synthesized by multicomponent 1,3-dipolar cycloaddition reaction of tetrahydroisoquinolinium N-ylides and (E)-3-arylidene-1-phenyl-pyrrolidine-2,5-diones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 72 publications
3
26
0
Order By: Relevance
“…These 88 structures show many different substitution patterns. The four structures with the most features in common with 1 are probably RAQCIY (Du et al, 2017), IFETAR (Guo et al, 2018), DOHMEV (Boudriga et al, 2019), and KIFRID (Zhang et al, 2018), though none of these are especially similar to 1.…”
Section: Database Surveymentioning
confidence: 99%
“…These 88 structures show many different substitution patterns. The four structures with the most features in common with 1 are probably RAQCIY (Du et al, 2017), IFETAR (Guo et al, 2018), DOHMEV (Boudriga et al, 2019), and KIFRID (Zhang et al, 2018), though none of these are especially similar to 1.…”
Section: Database Surveymentioning
confidence: 99%
“…After establishing the optimal conditions and screening many substrates, it was found that the regioselectivity (>60 : 40 rr ) was quite poor (Scheme 6). However, the use of halogen substituents, like Cl or Br, in the phenyl ring of isatin were beneficial for increasing regioselectivity (>90 : 10 rr ) in the synthesis of these new dispiropyrrolo[2,1‐ a ]isoquinoline‐fused pyrrolidine‐2,5‐dione derivatives bearing two adjacent spiro‐carbons [22] …”
Section: Spirooxindole Derivativesmentioning
confidence: 99%
“…Several research groups reported intermolecular (3+2)dipolar cycloadditions of electron-deficient alkenes and azomethine ylides derived from isatins and cyclic amines. [46][47][48][49] In addition to ,-unsaturated alkenes and aldehydes, fullerenes [50][51][52] and ,-unsaturated alkynes 53 are also viable dipolarophiles in (3+2) cycloadditions with azomethine ylides derived from the condensation of cyclic amines and aldehydes.…”
Section: Review Synthesismentioning
confidence: 99%